(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The polycaprolactone (PCL) known for its slow biodegradability shows potential applications in the field of skin scaffold production. In the current study PCL mats with micro scaled structure were produced via electrospinning and treated with NaOH solution for enhanced cell adhesion. The scaffolds were evaluated as an efficient stem cell growing material by human skin keratinocytes and fibroblasts culture. The cell viability assay (CellTiter-Blue) of the as spun scaffolds was compared with previously prepared PU electrospun scaffolds, fibrin scaffolds and amniotic membrane scaffold. Significant difference in cell adhesion was evident between the natural and synthetic scaffolds. As far as the electrospun scaffolds were concerned the significance between, as well as for the NaOH treated, samples was less evident. The repetition of different donor cells fluorescence within the same scaffold material was also present.